Development of an emergency volunteer-based call center for COVID-19 within the university setting - Hayu Qaimamunazzala (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
In response to concerns in the general public due to the Coronavirus Disease 2019 (COVID-19) pandemic, Universitas Gadjah Mada established a COVID-19 call center with the aid of volunteers. This study aims to describe the experience of developing and implementing an emergency volunteer-based call center addressing questions on COVID-19 by a higher academic institution along with the frequency and characteristics of the received calls in 2020. This descriptive observational study was conducted using secondary data to describe the implementation of a call center on COVID-19 at Universitas Gadjah Mada (UGM) between March and December 2020. Data were collected from organization documents and the caller response database. The data were analyzed descriptively. The development process included system development, volunteer recruitment, online training, and implementation. The volunteers logged a total of 150 calls during the 10-month study period. The highest frequency of calls was in March 2020 with 35 calls and the lowest was in August 2020 with only 3 calls. The majority of callers were from Yogyakarta and members of the UGM community. The main issues raised by callers were people seeking general information regarding COVID-19, recommendations regarding their health status, government and university policy related concerns, and logistics. Tele-outreach is a beneficial method to address public distress during a global pandemic, which could be managed with the aid of trained volunteers.